Liquid Organic Fertilizer Production Training As An Effort To Support Sustainable Agriculture: Pelatihan Pembuatan Pupuk Organik Cair Sebagai Upaya Mendukung Pertanian Berkelanjutan - Fia Audia; Imtitsal Maghfiroh; Muhammad Kaka Firmansyah; Aisyah Nur Jannah Putri Hariyono; Adisty Dwinda Trapsila; Prasmita Dian Wijayati (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2025)
Dependencies on chemical fertilizers and the limited knowledge of organic fertilizer production have become challenges in achieving sustainable agriculture. To address this issue, a community service activity was carried out on May 16, 2025, in Sedati Village, Ngoro District, Mojokerto Regency, involving ten members of a farmer group. In this activity, farmers were trained on how to produce and utilize Liquid Organic Fertilizer (LOF) made from organic waste. The methods used included counseling, interactive discussions, and hands-on practice in making LOF. Participants were taught how to use various materials such as fruits, rejected fish, fermented cassava yeast, palm sugar, eco-enzyme , and coconut water through a closed fermentation process lasting three months. As a result, participants were able to follow each stage effectively and understand the benefits of LOF in improving soil fertility, reducing production costs, and minimizing the use of chemical fertilizers. This initiative had a positive impact by encouraging farmer independence and promoting more environmentally friendly agricultural practices.